Psychological Well-Being in Broken Home Students - Ilhamuddin, Muhammad Farid (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Disharmony in a family, which is the result of a broken home, can have an impact on the level of individual psychological well-being. This study aims to describe the psychological well-being of students who experience broken homes. This study uses a qualitative method with a case study design. Participants were selected using a purposive sampling technique with the characteristics of students being male and coming from broken home families. There were three participants, namely BO, LC and STW. Collecting research data by means of in-depth interviews and participant observation. The results showed that the three participants had different aspects of subjective well-being. Psychological well-being BO is less positive while LC and STW are positive. The results of this study can be used as a reference regarding the development of effective inventions by taking into account the characteristics of the participants found.